Dealing in Dreams - Rivera, Lilliam (New York : Simon & Schuster BFYR, 2019)
"Sixteen year old Nalah leads the fiercest all-girl crew in Mega City, but when she sets her sights on giving this life up for a prestigious home in Mega Towers, she must decide if she's willing to do the unspeakable to get what she wants"--
Keywords: Teenage girls -- Juvenile fiction; Female gangs -- Juvenile fiction; Street life -- Juvenile fiction; Dystopias -- Juvenile fiction; Teenage girls -- Fiction; Female gangs -- Fiction; Street life -- Fiction; Dystopias -- Fiction; Science fiction